Search for ZH→l+l-bb̄ production in 4.2fb-1 of pp̄ collisions at √s=1.96TeV - Abazov, V. M. (2010)
We present a search for the standard model Higgs boson produced in association with a Z boson in 4.2fb⊃-1 of pp̄ collisions, collected with the D0 detector at the Fermilab Tevatron at √s=1.96TeV. Selected events contain one reconstructed Z→e⊃+e⊃- or Z→μ⊃+μ ⊃- candidate and at least two jets, including at least one b-tagged jet. In the absence of an excess over the background expected from other standard model processes, limits on the ZH cross section multiplied by the branching ratios are set. The limit at MH=115GeV is a factor of 5.9 larger than the standard model prediction. © 2010 The American Physical Society.